Student Perceptions of Tiktok Duet Challenge With Song as Media for Learning English Speaking - Rolita, Nita; Eryansyah, Eryansyah (Universitas Nurul Jadid, 2025)
AbstractThe integration of social media into education has grown rapidly, offering new opportunities for enhancing language learning. However, limited research has explored the specific use of TikTok Duet Challenges for developing English-speaking skills. This study aims to investigate students' perceptions of using the TikTok Duet Challenge with songs as a medium for learning English-speaking mastery, focusing on its effectiveness, benefits, and challenges within the English Education Study Program of a state-owned university of South Sumatra. A qualitative approach was employed, data were collected through interviews with eight students who had experience with the TikTok Duet Challenge with songs for English learning. The findings revealed that students perceived the TikTok Duet Challenge with songs as an engaging and effective tool for in improving pronunciation, fluency, and vocabulary in an enjoyable and low-pressure environment, significantly boosting their confidence and motivation. Students also reported that they appreciated the opportunity to engage with authentic language content and receive feedback through social interactions. However, some challenges were identified, including internet connectivity issues, fear of judgment, and difficulty understanding song lyrics. Despite these obstacles, students viewed the experience positively, indicating that TikTok Duet Challenges hold promise as a supplementary tool for enhancing English-speaking mastery. This study contributed to the discourse on technology-enhanced language learning and provides practical insights for educators integrating social media into instruction.